Predatory Efficiency of Diplonychus annulatum (Fabr.) (Hemiptera:Belostomatidae) on Developmental Stages of a Major Carp Catla catla (Ham.) - Ramanand, R.; Roy, S.P. (Our Nature, 2009)
The paper deals with the result of predatory efficiency of fed and starved (5, 7 and 9 days) groups of water bug Diplonychus annulatum (Fabr.) On spawn and fry stages of Catla catla (Ham.), a major carp of freshwater system in laboratory. The highest predation capacity (N/hr) on maximum spawn (25) densities were recorded as 8.40 ± 1.13, 7.80 ± 1.17, 6.10 ± 0.99, 5.60 ± 0.87 for fed and 5, 7 and 9 days starved predatory aquatic bug respectively. The predation was highest on maximum prey density (25) while it was minimized as the size of prey increased. It was also found that the rate of predatory efficiency was found more in natural feeding hour than the starved condition of this aquatic bug. Keywords: Predatory efficiency, Diplonychus annulatum (Fabr.), Spawn, Fry, Catla catla (Ham.) doi: 10.3126/on.v6i1.1649 Our Nature (2008)6:15-18